Braiding of religions: An approach to the experiences and interreligious dialogue in a local church - Irarrázaval, Diego (1996)
The Catholic population walks its own undulating paths and also travels on large highways. In the Andean South of Peru, universal Christianity is very particular, with inculturated and interculturated traits. This is one of many Latin American cases in which various types of beliefs, rites, and ethics intersect. It can be said that the common people have generated a polyreligious ecclesiality. A large part of the people defines themselves and registers in the Catholic field. But this is not uniform, since different religious currents are present.